Development of a Mathematics Dictionary as a Learning Media for Students in Elementary, Middle School and High School - Rosmaini, Rosmaini; Putri, Icha Elisyah; Sembiring, Putri Yolanda Br; Siringoringo, Rachel A; Siringoringo, Rona Maruli (EDUCTUM: Journal Research, 2024)
This research aims to develop learning media under the title "Development of a Mathematics Dictionary as a Learning Media for Students in Elementary, Middle School and High School". The aim of this research focuses on developing appropriate, effective and practical learning media in mathematics lessons. With the hope that the resulting product can provide optimal learning outcomes for each student and be useful for teachers in selecting learning media. This research uses a type of development research method, namely Research and Development. According to Sugiyono Research and Development is a research method used to produce certain products and test the effectiveness of these products. Research and Development functions to develop and validate products. Developing a product means updating/creating a new product (which has never existed before). Validating a product means that the product already exists, and researchers are only testing the validation or effectiveness of the product. So it can be concluded that the R&D method is a research method that produces the product you want to develop. The product that the author will develop is the Development of a Mathematics Dictionary as a Learning Media. This research uses a Research and Development design using the Borg and Gall model.